Emotional Granularity Effects on Event-Related Brain Potentials during Affective Picture Processing - Lee, Ja Y.; Lindquist, Kristen A.; Nam, Chang S. (Frontiers in Human Neuroscience, 2017)
There is debate about whether emotional granularity, the tendency to label emotions in a nuanced and specific manner, is merely a product of labeling abilities, or a systematic difference in the experience of emotion during emotionally evocative events. According to the Conceptual Act Theory of Emotion (CAT) (Barrett, 2006), emotional granularity is due to the latter and is a product of on-going temporal differences in how individuals categorize and thus make meaning of their affective states. To address this question, the present study investigated the effects of individual differences in emotional granularity on electroencephalography (EEG)-based brain activity during the experience of emotion in response to affective images. Event-related potentials (ERP) and event-related desynchronization and synchronization (ERD/ERS) analysis techniques were used. We found that ERP responses during the very early (60-90ms), middle (270-300ms) and later (540-570ms) moments of stimulus presentation were associated with individuals’ level of granularity. We also observed that highly granular individuals, compared to lowly granular individuals, exhibited relatively stable desynchronization of alpha power (8-12Hz) and synchronization of gamma power (30-50Hz) during the 3 seconds of stimulus presentation. Overall, our results suggest that emotional granularity is related to differences in neural processing throughout emotional experiences and that high granularity could be associated with access to executive control resources and a more habitual processing of affective stimuli, or a kind of “emotional complexity.” Implications for models of emotion are also discussed.